Integration of repositories in Moodle - Leal, José Paulo (2014)
Current Learning Management Systems focus on the management of students, keeping track of their progress across all types of training activities. This type of systems lacks integration with other e-Learning systems. For instance, learning objects stored in a centralized repository are unavailable throughout an organization for potential reuse. In this paper we present the interoperability features of crimsonHex - a service oriented repository of learning objects - highlighting the use of XML languages. Its nteroperability features are compliant with the existing standards and we propose extensions to the IMS interoperability recommendation, adding new functions, formalizing an XML message interchange and providing also a REST interface. To validate the proposed extensions and its implementation in crimsonHex we designed two repository plugins for Moodle 2.0, the first of which is already implemented and is expected to be included in the next release of this popular learning management system.